Meningkatkan Kemampuan Berpikir Matematis Siswa Melalui Model Pembelajaran Matematika Nalaria Realistik pada Madrasah Ibtidaiyah di Kota Sorong - Rusdin Rusdin (LPPM IAIN Sorong, 2019)
This study aims to capture and identify students of Islamic Education in the city of Sorong who have the competence in mathematics olympiad using the Realistic Mathematical Mathematics learning model (MNR). Through MNR, students will analyze mathematical thinking skills which include aspects of mathematical comprehension ability, mathematical communication, mathematical connections, and mathematical reasoning. The research subjects were 33 students of class V of Al Hidayah Science MI in Sorong City and two people in class VI. This study applies a design research method with three phases namely preliminary design, teaching experiment, and retrospective analysis. Data on students' mathematical thinking skills were obtained through pretest and posttest with descriptive data analysis at each phase. The results of the study in the preliminary design involving 35 students obtained pretest (1) an average of 9.74 and (2) standard deviation of 15.72. The experimental teaching results were obtained posttest (1) an average of 13.57; (2) standard deviation of 13.75 and (3) an increase of 39.32%. The retrospective analysis phase involved 7 students obtained from the results of pretest (1) 38.28 and standard deviation of 23.09. The posttest results were obtained (1) an average of 72.28; (2) standard deviation of 9.81; and (3) an increase of 88.77%. Thus the MNR model significantly contributes to improving students' mathematical thinking skills. Of the 7 students who participated in the final phase, 3 students had good abilities and 4 students had moderate abilities.